Sodium 3-phenylpropanoate alleviate oxidative stress and iron-induced testicular toxicity in Wistar rats - Akingbolabo Daniel Ogunlakin, Oluwafemi Adeleke Ojo, Matthew Iyobhebhe, Toluwanimi Lemuel Ajisafe, Emmanuel Olatunbosun Adeoye, Damilare Iyinkristi Ayokunle, Mubo Adeola Sonibare, Owoola Azeezat Ambali, Great Oluwamayokun Adebodun, Omolola Adenike Ajayi-Odoko, Tomi Lois Adetunji, Oluwafemi O. Oguntibeju (Journal of Applied Pharmaceutical Science, 2024)
There are various derivatives of cinnamic acid with pharmacological significance. Sodium 3-phenylpropanoate (KAD 1), a derivative of cinnamic acid, has also been synthesized and it is important to investigate its effects on iron-induced testicular injury in an ex vivo study. Evaluations were done on KAD 1’s l, l-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity, ferric-reducing antioxidant power, and iron chelating potential. Through the ex vivo incubation of tissue supernatant and 0.1 mM FeSO4 for 30 minutes at 37°C and various concentrations of KAD 1, oxidative testicular damage induced was treated. The scavenging property of KAD 1 increases significantly (p < 0.05) as the concentration increases when compared with the standard quercetin. The malondialdehyde, catalase, ATPase, as well as ENTPDase activities, were reduced when testicular damage was induced (p < 0.05). A significant rise in glutathione level was observed. Therefore, KAD 1 has the potential to treat and protect against oxidative testicular toxicity, as revealed by its capacity to control nucleotide hydrolysis and reduce oxidative stress. Thus, KAD 1 may be a suitable potent modality, which can help treat testicular injury.
Keywords: Sodium 3-phenylpropanoate (KAD 1), iron-induced testicular injury, ATPase, ENTPDase